Silicon–SAM–AuNP electrodes: Electrochemical “switching” and stability - Kashi, M.; Wu, Y.; Gonçales, V.; Choudhury, M.; Ciampi, Simone; Gooding, J. (Elsevier Inc., 2016)
The immobilization of gold nanoparticles (AuNPs) on functionalized electrodes has been shown to be an effective way for switching on the electrochemistry at an otherwise passivated surface. Herein, the attachment of AuNPs onto the industrially available p+- Si(100) electrodes was studied by means of cyclic voltammetry and X-ray photoelectron spectroscopy. The hydrosilylation of p+-Si(100) with 1,8-nonadiyne followed by the “click” of azido propylamine onto the alkyne end formed a self-assembled monolayer (SAM), which protected the p+-Si(100) against oxidation and prevented the electron transfer from dissolved Ru(NH3)63 +. Upon the attachment of AuNPs, however, electron transfer was initially restored. The performance of the p+–Si–SAM–AuNP electrode was found to decay with repeated voltammetric cycling due to the formation of SiOx underneath the SAM. These results suggest that p+–Si–SAM–AuNP electrodes can be used in electrochemical devices for single use applications but are not suitable for long-term use.